ROLE OF CBCT IN ORAL AND MAXILLOFACIAL SURGERY – A REVIEW - Monsy, Merlyn Elizabeth; Maini, Anuj Paul; Kollipara, Jeevana; Tiwari, Rahul VC; Gulia, Sunil Kumar; Patel , Sumaiyya (International Journal of Psychosocial Rehabilitation, 2020)
The technological innovation have always been a boon to the mankind. Ever since the discovery of radiation in the year 1885 (Wilhelm Conroed Roentgen),there were enormous increase in diagnostic imaging technology. One such imaging which sweeped changes in field of dentistry is CBCT(Cone beam computer tomography).With no doubt it serves specific application in oral and maxillofacial surgery(OMFS).This article review the implications of CBCT in the diagnostic and operative procedure in OMFS by compiling the information from various databases such as articles and textbooks.